ANALISIS MANAJEMEN RANTAI PASOK (SUPPLY CHAIN MANAGEMENT) SAYURAN DI KAMPUNG 6 UNTUK MENINGKATKAN KESEJAHTERAAN PETANI - -, Nurhaliza; Hidayat, Nurul; Armanita, Nabila; Asnawia (tesco publisher, 2024)
This research analyzes the supply chain management (SCM) of vegetables in Kampung 6 to improve farmers' welfare. SCM plays an important role in ensuring the efficiency of the vegetable distribution flow from farmers to consumers, especially considering that vegetables are perishable commodities. The research used qualitative methods with observation, interview, and documentation techniques. Data was analyzed inductively to find patterns and relationships in the distribution flow. The results showed that limited coordination and lack of technology caused inefficiencies in the supply chain, such as distribution delays and increased operational costs. The implementation of SCM with the support of information technology has the potential to improve operational efficiency, maintain product quality, and increase farmers' bargaining power. Recommendations for this study include improving coordination between supply chain actors and utilizing technology for better distribution management, which in turn is expected to improve the welfare of farmers in Kampung 6.